Comparative Analysis of Image Enhancement Techniques for Ultrasound Liver Image - Smriti Sahu; Maheedhar Dubey; Mohammad Imroze Khan (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Liver cancer is the sixth most common malignant tumour in the world and the third most common cause of cancer-related deaths worldwide. To diagnose such liver diseases, In this paper comparison has been made for various image enhancement techniques that are applied to liver ultrasound image. Three types of liver ultrasound images used are normal, benign and malignant liver images. The techniques, which are compared on the basis of two evaluation parameters Peak Signal to Noise Ratio (PSNR) and Mean Square Error (MSE) including, Contrast Stretching, Shock Filter, Histogram Equalization, Contrast Limited Adaptive Histogram Equalization (CLAHE).Such a comparison would be helpful in determining the best suited method for clinical diagnosis. It also has been observed that the Shock filter gives the better performance than others for liver ultrasonic image analysis.DOI:http://dx.doi.org/10.11591/ijece.v2i6.1513